Grammatical Cohesion in the Novel "Hallowe'en Party" - Ida Bagus Gede Dwitya Dharma Suputra; Ni Wayan Sukarini; Putu Weddha Savitri (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study is aimed to classify a text into four types of grammatical cohesion and to explain the conditions concerning each of their occurrences in the text. It uses the theory by Halliday and Hasan about cohesion (1976) as its main theory. The data of this study, which is the text of a novel, was collected by using documentation method. Then, the data analysis was conducted using qualitative method. Finally, the data analysis was presented using an informal method in the form of descriptions and explanations based on the four types of grammatical cohesion. The analysis results show the classifications of all the four types of grammatical cohesion along with each of their sub-categories found in the data. Additionally, it also includes the explanations concerning the occurrences of those types of grammatical cohesion within the data.